Kinetics of arylation of 3-bromo-benzophenone with n-butylacrylate using NC palladacycle catalyst - Atla, Shashi B.; Rajurkar, Kalpendra B.; Kelkar, Ashutosh A.; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A-Chemical, 2009)
The kinetics of arylation of n-butylacrylate (n-BA) with 3-bromo-benzophenone (BBP) using a monomeric palladacycle complex [Pd(ppy)(PPh(3))(OTs)](ppy=2-phenylpyridine) catalyst has been studied. The effect of concentration of the substrate, base (NaOAc), and catalyst was studied at three different temperatures (413-433 K). The rate was found to be first order with respect to catalyst, first order tending to zero order with respect to n-butylacrylate and NaOAc concentrations. The rate passed through a maximum with variation of BBP concentration. The observed results have been explained on the basis of formation of Pd species (PdX(2), PdX(3)(-), PdX(4)(2-), and Pd(2)X(6)(2-)) which are inactive for the Heck reaction. Various empirical rate equations were considered to fit the rate data and the best fitting model has been selected. The rates predicted by model were found to be in good agreement with the observed experimental data. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Arylation; Heck reaction; kinetics; Palladacycle

Kinetics of hydroformylation of 1-octene in ionic liquid-organic biphasic media using rhodium sulfoxantphos catalyst - Deshpande, R. M.; Kelkar, Ashutosh A.; Sharma, A.; Julcour-Lebigue, C.; Delmas, Henri (Chemical Engineering Science, 2011)
Biphasic hydroformylation of 1-octene was performed using rhodium sulfoxantphos catalyst dissolved in [BuPy][BF(4)] ionic liquid. Preliminary experiments proved this system to retain the catalytic complex within the ionic liquid phase and to maintain a high selectivity towards the linear aldehyde (n:iso ratio of 30) over several cycles. Process parameter investigation showed a first order dependence of the initial rate with respect to the catalyst and 1-octene concentrations, but a more complex behavior with respect to hydrogen (fractional order) and carbon monoxide partial pressures (inhibition at high pressures). Different mathematical models were selected based on the trends observed and evaluated for data fitting. Also, rate models were derived from a proposed mechanism, using Christiansen matrix approach. To calculate concentrations of substrates in the catalytic phase as required by this kinetic modeling, solubility measurements were preformed for the gases (pressure drop technique), as well as for 1-octene and n-nonanal (thermogravimetry analysis). (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biphasic catalysis; Butylpyridinium tetrafluoroborate; kinetics; Parameter identification; Reaction engineering; solubility